The Effect of Profitability, Leverage and Company Size on Corporate Tax Avoidance - Annisa Shafira; Hasim As’ari (Journal of Social Research, 2023)
Indonesia is a nation that uses taxes as a means of supporting its state treasury. As a tax collection tool, Indonesia uses various types of taxes. The value of the tax is determined from the results of the collection of public funds, and the tax is then used as a condition for carrying out state development. The study sought to ascertain how profitability, leverage, and company size affect tax evasion. The approach used in this study is qualitative and involves collecting information from cigarette manufacturers listed on the IDX for the years 2016 to 2021. The findings of this study show that although leverage has little impact on tax evasion, profitability has little impact.